Meeting Report: 31st International Mammalian Genome Conference, Mammalian Genetics and Genomics: From Molecular Mechanisms to Translational Applications - Sánchez-Andrade, Gabriela (Mamm Genome, 2018)
High on the Heidelberg hills, inside the Advanced Training Centre of the European Molecular Biology Laboratory (EMBL) campus with its unique double-helix staircase, scientists gathered for the EMBL conference “Mammalian Genetics and Genomics: From Molecular Mechanisms to Translational Applications”, organized in cooperation with the International Mammalian Genome Society (IMGS) and the Mouse Molecular Genetics (MMG) group. The conference attracted 205 participants from 30 countries, representing 6 of the 7 continents –all except Antarctica. It was a richly diverse group of geneticists, clinicians and bioinformaticians, with presentations by established and junior investigators, including many trainees. From the 24(th)-27(th) of October 2017, they shared exciting advances in mammalian genetics and genomics research, from the introduction of cutting-edge technologies to descriptions of translational studies involving highly relevant models of human disease.